The Current State of Climate Change Perceptions and Policies in Myanmar: 2014 Report - McKinley, J.; Adaro, C.; Pede, Valerien O.; Setiyono, T.; Aung, N.M.; Htwe, N.M.; Nyo, M.H.; Than, S.M.; Hom, N.H.; Swe, K.L.; Quicho, E.; Sheinkman, Michael; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This report was constructed to assess the current perceptions and policies regarding climate change in Myanmar. It is comprised of a country report outlining current policies relating to climate change, as well as results from two stakeholder perception surveys conducted at the local and national level in Myanmar. The stakeholder perception survey was administered to 33 local stakeholders and 12 national stakeholders from government organizations, farmers’ groups, universities, and research institutes. Results indicate that the primary concern regarding climate change is mostly concentrated on rainfall trends, such as drought and flooding. In addition, local stakeholders have concerns over heat stress, whereas national stakeholders are less concerned with the issue. Only 11 local stakeholders report that their institution currently has a division or staff member working on climate change issues. Seven of 12 national stakeholders reported that their institutions did have a division or staff member working on climate change issues.